2017
DOI: 10.32598/jccnc.3.3.231
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Social Interactions in Patients With Hepatitis B Infection: A Grounded Theory Study

Abstract: Background: The hepatitis B virus infection is a major cause of liver diseases in the world. It mostly affects psychological and social aspects as well as the mental health of patients. The aim of this study was to explain the process of social interactions in patients with Hepatitis B Virus (HBV) infection. Methods: The present study was conducted using the grounded theory method from 2014 to 2016 in the Amol, Babol, and Tabriz health and counseling centers. The data was collected using in-depth semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In Malaysia and Cameroon, studies revealed that patients reacted with shock when unexpectedly diagnosed with hepatitis B 11 18. These reactions were due to an unexpected HBV diagnosis 12. A similar study in Ghana reported that individuals were astonished to identify that they had hepatitis B 10.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Malaysia and Cameroon, studies revealed that patients reacted with shock when unexpectedly diagnosed with hepatitis B 11 18. These reactions were due to an unexpected HBV diagnosis 12. A similar study in Ghana reported that individuals were astonished to identify that they had hepatitis B 10.…”
Section: Discussionmentioning
confidence: 99%
“… 11 18 These reactions were due to an unexpected HBV diagnosis. 12 A similar study in Ghana reported that individuals were astonished to identify that they had hepatitis B. 10 In relation to pregnancy, studies highlighted that pregnant women with chronic hepatitis B infection had higher levels of anxiety and stress than healthy pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations